Modern Asian studies
Modern Asian Studies promotes original, innovative and rigorous research on the history, sociology, economics and culture of modern Asia. Covering South Asia, South-East Asia, China, Japan and Korea, the journal is published in six parts each year. It welcomes articles which deploy inter-disciplinary and comparative research methods. Modern Asian Studies specialises in the publication of longer monographic essays based on path-breaking new research; it carries substantial synoptic essays which illuminate the state of the broad field in fresh ways, and also publishes longer review essays that discuss important new books.